Trade‐Offs Among SDGs: How the Pursuit of Economic, Food, and Urban Development Goals May Undermine Climate and Equity Targets? - Walter Leal Filho (741384) (2025)
The United Nations Sustainable Development Goals (SDGs) provide a comprehensive framework for addressing global challenges; however, their implementation reveals critical tensions between development priorities and climate action that warrant deeper examination. Indeed, one significant factor impacting the implementation of the SDGs is the presence of conflicts between certain goals. Accordingly, this study aims to critically examine how the pursuit of economic growth (SDG 8), food security (SDG 2), clean energy (SDG 7), and urban development (SDG 11) may exacerbate climate change and environmental degradation (SDGs 13–15) while also reinforcing social inequalities (SDGs 6, 10). Employing a review‐based approach to assess SDG interactions—focusing on the climate‐development nexus, particularly the relationship between economic expansion (SDG 8), environmental sustainability (SDGs 13–15), and social equity (SDGs 1, 5, and 10)—this research identifies key areas of conflict that challenge the framework's internal coherence. Findings indicate significant trade‐offs between economic growth and environmental sustainability, alongside previously underexamined tensions between social equity goals and resource‐intensive development strategies. Accordingly, the study proposes a roadmap for resolving these tensions through integrated climate governance, targeted interventions, and cross‐sectoral decision‐making that aligns development with the Paris Agreement and the 2030 Agenda. The practical implications of the study are twofold. First, it triggers a reflection on the root causes of conflicting goals, a serious problem that has been largely overlooked. Second, it highlights the importance of addressing the need to pay more attention to existing conflicts, as they have adverse effects that should be avoided. By offering actionable recommendations, this study contributes to the evolving discourse on sustainable development within the context of climate change mitigation and adaptation. It provides a strategic pathway toward balancing economic development with environmental resilience, ensuring that SDG implementation aligns with the urgent need for climate action within the remaining timeframe before 2030. Other Information Published in: Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/sd.70029